Metodo e ricerca in medicina e psichiatria - Riggio, Martino (Il sogno della farfalla, 2008)
The author points out that throughout history medical research has always had difficulty in recognizing an external noxa responsible for the illness. In psychiatry the idea of an external cause is still not accepted, but on the other hand, in alliance with the dominant culture, an illness which is ever-present and always controlled by reason and by the conscience that lies within man is continuously proposed. The author acknowledges that the rebellion to false ideologies and false beliefs is an essential characteristic of every researcher.